Acupuncture Therapy Study in Obesity Cases: Glycemic and Inflammatory Marker Patterns - Sumanto; Suwaji Handaru W; Sholichan Badri (Jurnal Penelitian Pendidikan IPA, 2025)
Obesity is a problem in various countries, not only in developed countries but also in developing countries. Central obesity occurs due to excessive fat accumulation in the upper body, especially in the abdomen, which is generally in men and is characterized by an increase in waist circumference. Central obesity occurs due to excessive adipocyte expansion which can cause hypoxia and oxidative stress, resulting in further inflammation. Obesity can cause coronary heart disease, hypertension, stroke, insulin resistance, Diabetes Mellitus (DM), hyperlipidemia and cancer. This study aims to determine glycemic and inflammatory markers and obtain acupuncture therapy models in obesity cases. This study was designed as a quasi-experiment using the Pre-Post Design with obesity cases. The study was conducted in 3 stages (three years). Each series of acupuncture therapy was carried out 8 times. This study was conducted in three series (for 3 years, each year 1 series of acupuncture therapy). Haematologic and lipid examinations were carried out 2 times before therapy and after the 8th therapy in the first year. Liver function tests, insulin hormone tests and HBA1C tests were performed twice before therapy and after the 8th therapy in the second year. Kidney function tests were performed twice before therapy and after the 8th therapy in the third year. Laboratory results were analyzed using SPPS 23 statistical software to see their significance. Laboratory values were used in mathematical modeling to obtain the right acupuncture therapy model for obesity cases.